# Splitting the middle term of : 2x^2+5/3x-2

## Answers

**Step-by-step explanation:**

Step-1 : Multiply the coefficient of the first term by the constant 6 • -6 = -36

Step-2 : Find two factors of -36 whose sum equals the coefficient of the middle term, which is 5 .

-36 + 1 = -35

-18 + 2 = -16

-12 + 3 = -9

-9 + 4 = -5

-6 + 6 = 0

-4 + 9 = 5 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -4 and 9

6x2 - 4x + 9x - 6

Step-4 : Add up the first 2 terms, pulling out like factors :

2x • (3x-2)

Add up the last 2 terms, pulling out common factors :

3 • (3x-2)

Step-5 : Add up the four terms of step 4 :

(2x+3) • (3x-2)